2020
DOI: 10.1097/jxx.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Educational interventions for primary care providers to improve clinical skin examination for skin cancer

Abstract: Background and Purpose: Skin cancer, the most commonly diagnosed cancer in the United States, is a serious health care concern. Early skin cancer detection improves prognosis; most common early detection approach is a comprehensive clinical skin examination (CSE). A CSE consists of skin cancer risk assessment, head-to-toe skin examination, and skin lesion assessment. Nurse practitioners (NPs) currently lack adequate training and confidence to conduct CSE. The goal of this systematic review was to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…In a study describing tobacco control measures, implementing a new policy influenced attitudes, beliefs, and behaviours, which in turn influenced health outcomes [32]. Description of a new model at an early stage of implementation is unusual, and addresses the issue that methods of skin cancer initiative implementation are rarely described, as has been raised previously [19]. Member checking with the key stakeholders utilised the logic model as a visual aid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study describing tobacco control measures, implementing a new policy influenced attitudes, beliefs, and behaviours, which in turn influenced health outcomes [32]. Description of a new model at an early stage of implementation is unusual, and addresses the issue that methods of skin cancer initiative implementation are rarely described, as has been raised previously [19]. Member checking with the key stakeholders utilised the logic model as a visual aid.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer self-examination with the naked eye or mobile teledermoscopy have also been trialled [ 18 ]. A recent systematic review highlighted that primary care provider clinical skin examination interventions are rarely evaluated for efficacy or effectiveness, and implementation methods tend to be poorly described [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, educational interventions may increase knowledge regarding skin cancer and melanoma detection. However, Stratton and Loescher (2020) performed a systematic review to identify published interventions that pertained to clinical skin examination for skin cancer identification by primary care nurse practitioners. They reviewed 10 articles and found that existing educational interventions regarding skin cancer were not tested for efficacy or effectiveness.…”
Section: Available Knowledgementioning
confidence: 99%
“…Moreover, the confidence of both practitioners and students increases with exposure to educational programs promoting skin cancer prevention and detection (Bort, 2021; Chen et al, 2015; Guégan et al, 2021). However, access to educational programs on skin cancer detection and treatment for current and future primary care providers continues to be limited (Eide et al, 2013; Hartnett & O'Keefe, 2016; Stratton & Loescher, 2020).…”
Section: Background and Significancementioning
confidence: 99%
“…The incidence of melanoma is increasing, and mortality from late-stage diagnosis continues to be a concern. Primary care providers face barriers to early detection and prevention of cutaneous cancers in daily practice and include a lack of training in full skin examinations (FSEs), lesion recognition, and treatment options (Azima, 2016; Herath et al, 2018; Stratton & Loescher, 2020). Research suggests that targeted educational programs for primary care providers on skin cancer can improve knowledge, confidence, and clinical skills (Hartnett & O'Keefe, 2016; Loescher et al, 2018).…”
mentioning
confidence: 99%